The Effectiveness of Six Weeks of Core Stability Exercises on Q Angle and Flatfoot in Female Taekwondo Athletes - Ebrahim Ebrahimi; Parnian Rashidi; Neginsadat Tabatabaei; Narges Soleymani (Biyumikānīk-i varzishī)
Objective Taekwondo is an Olympic combat sport that, due to its intense and complex training, exposes athletes to lower limb abnormalities. Performing corrective exercises to address these issues is essential, and core stability exercises appear to be effective. Therefore, the aim of the present study was to examine the impact of six weeks of core stability exercises on the Q angle and flatfoot in female taekwondo practitioners. Methods This quasi-experimental study was conducted in the field. The statistical population consisted of 30 female taekwondo practitioners, aged 15–25, from Mashhad, who were purposefully selected and randomly divided into two groups of 15. The Staheli arch index was used to assess flatfoot, and a goniometer was employed to measure the Q angle. A pre-test was conducted to measure the variables of interest, followed by a six-week core stability training program for the experimental group. A post-test was administered using the same procedures as the pre-test. Results The results indicated that the six-week exercise program significantly improved flatfoot (P = 0.001) and reduced the Q angle (P = 0.001) in the experimental group compared to the control group. Conclusion Core stability exercises can be effective in addressing abnormalities and rehabilitating athletic performance. This study aimed to investigate the impact of six weeks of core stability exercises on improving flatfoot and reducing the Q angle in female taekwondo practitioners. The results of this study showed that core stability exercises improved flatfoot and reduced the Q angle in female taekwondo practitioners. It is recommended that core stability exercises be incorporated alongside regular taekwondo training to improve balance and enhance performance.